Increased expression of SYCP2 predicts poor prognosis in patients suffering from breast carcinoma - Zheng, Hongyan; Guo, Xiaorong; Li, Nan; Qin, Luyao; Li, Xiaoqing; Lou, Ge (Frontiers in Genetics, 2022)
Overexpression of Synaptonemal complex protein-2 (SYCP2) has been identified in various human papillomavirus (HPV)-related carcinomas, whereas its significant role in breast carcinoma remains unclear. The aim of this study was to elucidate the prognostic value and potential function of SYCP2 in breast carcinoma. Herein, data for breast carcinoma patients originated from the Gene Expression Omnibus (GEO) and Carcinoma Genome Atlas database (TCGA) were analyzed. Kaplan-Meier analysis, Cox regression, and Receiver operating characteristic (ROC) curves were employed for determining the predictive value of SYCP2 on clinical outcomes in patients suffering from breast carcinoma. A nomogram was generated to predict the effect arising from SYCP2 on prognosis. The enrichment analysis of SYCP2 including Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), functional similarities, and GSEA were performed. The association analysis of SYCP2 gene expression and diverse immune infiltration levels was conducted through ssGSEA and ESTIMATE analysis, which consisted of dendritic cell (DC), neutrophil, eosinophil, macrophage, mast cell, NK cell and other 18 cell subtypes. The results showed that SYCP2 expression was significantly elevated in breast carcinoma tissues as compared with normal tissues (P<0.001). Kaplan-Meier survival analysis showed that patients suffering from breast carcinoma characterized by high SYCP2 expression had a poorer prognosis than patients with low SYCP2 expression (P=0.005). SYCP2 played a certain role in pathways related to DNA methylation, keratinocyte differentiation, steroid hormone biosynthesis and immune infiltration. The high expression of SYCP2 had a significant relationship to age, pathological type, ER expression and PR expression (P<0.001). Univariate and multivariate analyses revealed that SYCP2 had an independent relationship to overall survival (P=0.049). Moreover, ROC curves suggested the significant diagnostic ability of SYCP2 for breast carcinoma, and as time went on SYCP2 had more accurate prognostic efficacy. Furthermore, a high level of SYCP expression was found to have a relationship to poor prognosis of breast carcinoma in the subgroups of T3, N0, M0, and infiltrating ductal carcinoma (HR>1, P<0.05). Conclusively, SYCP plays a vital role in the pathogenesis and progression of human breast carcinoma, so it may serve as a promising prognostic molecular marker of poor survival.